Central Tethyan platform-top hypoxia during Oceanic Anoxic Event 1a - Hüter, Alexander (Dr. rer. nat.); Huck, Stefan (Dr. rer. nat.); Bodin, Stéphane (Prof. Dr. rer. nat.); Heimhofer, Ulrich (Prof. Dr. rer. nat.); Weyer, Stefan (Prof. Dr. rer. nat.); Jochum, Klaus P. (Dr. rer. nat.); Immenhauser, Adrian (Prof. Dr.) (2019)
Short-term hypoxia in epeiric water masses is a common phenomenon of modern marine environments and causes mass mortality in coastal marine ecosystems. Here, we test the hypothesis that during the early Aptian, platform-top hypoxia temporarily established in some of the vast epeiric seas of the central Tethys and caused, combined with other stressors, significant changes in reefal ecosystems. Potentially interesting target examples include time intervals characterized by the demise of lower Aptian rudist–coral communities and the establishment of microencruster facies, as previously described from the central and southern Tethys and from the proto-North Atlantic domain. These considerations are relevant as previous work has predominantly focused on early Aptian basinal anoxia in the context of Oceanic Anoxic Event (OAE) 1a, whereas the potential expansion of the oxygen minimum zone (OMZ) in coeval shallow-water environments is underexplored. Well-known patterns in the \(δ_{13}C\) record during OAE 1a allow for a sufficiently time-resolved correlation with previously studied locations and assignment to chemostratigraphic segments. This paper presents and critically discusses the outcome of a multi-proxy study (e.g., rare earth elements (REEs), U isotopes, and redox-sensitive trace elements) applied to lower Aptian shallow-water carbonates today exposed in the Kanfanar quarry in Istria, Croatia. These rocks were deposited on an extensive, isolated high in the central Tethys surrounded by hemipelagic basins. Remarkably, during chemostratigraphic segment C2, the depletion of redox-sensitive trace elements As, V, Mo, and U in platform carbonates, deposited in normal marine oxic waters, record the first occurrence of basinal, organic-rich sediment deposition in which these elements are enriched. During the C3 segment, seawater oxygen depletion established on the platform top as indicated by the patterns in Ce/Ce\(^{∗}\) and U isotopes. Shifts in redox-sensitive proxies coincide with the expansion of ...